Platelet-rich Plasma Therapy as a Treatment for Unilateral Foot Pain in a Child - Aanchal Sharma; Akhil Bhalla; Ishwar Bohra (Indian Journal of Pain)
Lateral sprains have been commonly seen in ankle injuries and have been the leading cause of chronic pain, disability, and posttraumatic ankle osteoarthritis. Other than conventional conservative measures, platelet-rich plasma (PRP) therapy has gained a lot of success in achieving complete healing along with pain relief and improvement in functional outcomes. Its use in the pediatric population has also shown promising results. Here, we report the case of a 12-year-old child who had a partial tear of the anterior talofibular ligament (ATFL) and had tried conservative measures for 2 years with no relief. The pain continued to worsen limiting any sports activities. We performed two PRP injections in ATFL 4 weeks apart under direct visualization of ultrasonography. This case report adds to the current evidence of the beneficial effects of PRP on old ligament injury and its utility in the pediatric population.